Formalizing the names of subfamilies and tribes of ponyfishes (Leiognathidae Gill 1893) - Chakrabarty, Prosanta; Sparks, John S. (Zootaxa, 2015)
Several higher-level clades (subfamilies and tribes) of ponyfishes were introduced and diagnosed without the term “new” following the taxon names and without reference to a type genus. We correct these errors here so that the clade names comply with Articles 16.1 and 16.2, and Recommendation 16A of the Code (ICZN 2000, 4th edition), and may be formally recognized. Diagnoses for all of these clades were presented in Chakrabarty et al. (2011) and their membership updated in Sparks and Chakrabarty (2015).